Acclimation process of marathon athletes for the Tokyo Olympic Games 2020 - Cupido Santos, A.; Afonso, J.; Gaspar, A. R.; Da Silva, M. G. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Women`s marathon of Tokyo Olympic Games 2020 was held on the 7th of August in Sapporo, Japan. This region has recorded, exactly in this day its highest temperature in 21 years, at 6 a.m. at the start of the race, the sky was clear, the temperature was 25 °C and a relative humidity was 82%. The temperature rose during the competition to above 30°C with relative humidity above 80%, which means values of WBGT exceeding 30, already in the dangerous category. With this type of warning, the acclimatization process becomes essential in an athletes sports preparation, not only to improve sport performance but also to preserve physical integrity.